2013
DOI: 10.1136/jech-2013-202685
|View full text |Cite
|
Sign up to set email alerts
|

Political and economic characteristics as moderators of the relationship between health services and infant mortality in less-developed countries

Abstract: Our study provides additional evidence that democracy has direct effects on IMR and further showed that democracy can modify the effects of health services on IMR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
2

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 29 publications
0
8
0
2
Order By: Relevance
“…Studies have found associations between HDI and health system quality, health outcomes, disease prevalence, and health-seeking behavior ( 20 24 ). Polity has been associated with health metrics such as healthcare expenditures and infant mortality ( 25 , 26 ).…”
Section: Methodsmentioning
confidence: 99%
“…Studies have found associations between HDI and health system quality, health outcomes, disease prevalence, and health-seeking behavior ( 20 24 ). Polity has been associated with health metrics such as healthcare expenditures and infant mortality ( 25 , 26 ).…”
Section: Methodsmentioning
confidence: 99%
“…Their wide availability allows for large samples of less-developed countries to be used, thus, answering a critique of many existing studies (Farag et al 2013). Thus, this study will follow previous studies and utilize a country’s infant mortality rate to approximate the health of its population (e.g., K.-Y. Chuang, Sung, Chang, and Chuang 2013; Y.-C. Chuang, Sung, Chao, et al 2013; Houweling et al 2005; London and Williams 1990; Moon and Dixon 1985; J.…”
Section: Infant Mortality: Cross-national Trends and Determinantsmentioning
confidence: 99%
“…In the last three decades, democracy has been identified as one of these structural factors that may explain health disparities in developing countries. A variety of health indicators have been used to assess the relationship between democracy and health, such as life expectancy or healthy life expectancy (Besley and Kudamatsu 2006; Franco, Álvarez-Dardet, and Ruiz 2004; Ghobarah, Huth, and Russett 2004a, 2004b; Lena and London 1993; Navarro et al 2003; Reidpath and Allotey 2006), the mortality rate (Franco et al 2004; Lake and Baum 2001; Li and Wen 2005; McGuire 2006; Navarro et al 2003; Navia and Zweifel 2003; Safaei 2006; Zweifel and Navia 2000), and infant and child mortality (K.-Y. Chuang, Sung, Chang, and Chuang 2013; Y.-C. Chuang, Sung, Chao, et al 2013; Houweling et al 2005; London and Williams 1990; Moon and Dixon 1985; J.…”
Section: Introductionmentioning
confidence: 99%
“…The American study showed that improvements in primary care expressively influenced IMR and the number of underweight children in the US, thus demonstrating a negative association between the implementation of primary health care and reduction in infant mortality in the USA [12]. However, few studies have discussed how political and economic contexts shape the effects of health and environment, so that a politically and economically unstable society would have difficulties with transferring health resources for effectively implementing care measures for the populations' health, in spite of this society having a sufficient number of professionals and health facilities to meet these requirements [13]. Therefore, research has the important task of reducing maternal mortality and its multi-causal factors around the world.…”
Section: Introductionmentioning
confidence: 99%